Literatur Review: Effectiveness of Back Massage Therapy on Reducing Pain Intensity in Elderly with Low Back Pain - Nurul Huda; Bagus Dwi Cahyono; Evy Aristawati (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Low back pain is one of the musculoskeletal disorders due to poor activities that cause pain that is often suffered by the elderly. Back pain is a structure originating from the spine, namely in the spinal area (lower back), muscles, nerves or others around the area. Usually accompanied by radiating from the feet and legs. One of the efforts to reduce the intensity is by doing a back massage. Massage stimulation can release the body to release endorphins which are natural pain relievers and generate nerve fibers that close the synaptic gate so that impulses to the spinal cord and brain are inhibited. this study was to determine the effectiveness of back massage therapy on reducing the intensity of low back pain in the elderly. used in this final report is a literature review by reviewing 2 international articles and 8 national articles, the data collection process uses the PRISMA (Preferred Reporting Items For Systematic Review and Meta Analysis) method and performs data analysis using Thematic Analysis with doing the stages of comparing, contrasting, and criticizing, got the results that, 10 journal articles that the author took for literature review research. back massage therapy can reduce back pain in the elderly. The results of the review showed that 10 articles demonstrated a reduction in back intensity. Lower back pain has decreased due to touch as a stimulus to relax, then a relaxation response will appear in the back area so that you can rest in peace and the level of pain felt has decreased.